Importance of clinical and radiological assessment of patient of osteoarthritis knee foroptimum outcome in total knee replacement - Kundu, Soutrik; Dakshit, Kosturi; Garg, Rohit Nirbhay; Dussa, Kumarswami Ramulu (International Journal of Research in Orthopaedics, 2024)
Background: Total knee replacement (TKR) provides symptomatic relief in patients with severe arthritis by removing pathologic joint tissue and restoration of the joint anatomy and function by the replacing with metal or plastic components leading to more stable biomechanics. Inspite of all advances in the surgical techniques 1 out of 5 people who undergo TKA remain unsatisfied. Clinical and radiological grading of osteoarthritis of knee may be an important prognostic marker to assess the outcome following TKR. Methods: Study conducted was retrospective study. Pre-op routine and clinical assessment data noted from departmental records. Correlation between ‘initial knee society score’ (KSSi) and ‘radiological severity’ in terms of (Kellgren-Lawrence) grade and varus angle with ‘change in knee society score’ (ΔKSS) assessed to reach at conclusion. Results: Lower KSS values, higher KL grading, higher femorotibial angle and were associated significantly with higher change in KSS values, i.e. better outcome. Conclusions: Severe OA knee with high FTA and higher KL grade has shown better outcome following TKA. In early stages it is better to manage the patient conservatively with medications and physiotherapy.